Cover Picture: Design and Enantioselective Synthesis of Cashmeran Odorants by Using "Enol Catalysis" (Angew. Chem. Int. Ed. 6/2015). Issue 6 (9th January 2015) - Felker, Irene; Pupo, Gabriele; Kraft, Philip; List, Benjamin
<x xml:space="preserve">Abstract</x> Cashmere Wood is the term used for the typical odor of Cashmeran, which is found in perfumes, such as "Dans Tes Bras". In their Communication on page 1960 ff., B. List, P. Kraft, and co‐workers describe the design of novel Cashmeran odorants and their stereoselective synthesis through enol activation. The key transformation is a chiral phosphoric acid catalyzed Michael addition of enones to α‐substituted ketones. The results grant insight into the structure–odor correlations of these odorants.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>